Advanced Technologies for Detection and Assessment of Road Degradation State. Experimental and Modeling Approaches - Crăciunescu Dan; Racanel Carmen; Ionița Stefan; Sandu Robert; Niculescu Mariana; Sicoe George (Romanian Journal of Transport Infrastructure, 2023)
Detection and classification of degradation types is a fundamental activity in road pavement management. Monitoring activities through manual / visual inspections are time consuming, costly and cause safety issues. The introduction of new high-efficiency equipment for the detection and classification of degradation opens a new perspective in the analysis and management of roads. Thus, the automatic monitoring of the road asset introduces new performance indicators and more complex criteria for classifying problems. In this paper, an analysis is presented by referring to examples of measurements in Romania, detection, and classification of the main types of degradation, study, and capabilities of ACD (Automatic Crack Detection). A numerical and experimental study was also conducted to improve the operational optimization of ACD equipment to increase its usability and performance.